Pemberdayaan Ekonomi Melalui Pendampingan Penerapan Akuntansi Sederhana pada UMKM Masyarakat Desa Tanjungsari - Dianwicaksih Arieftiara; Masripah Masripah; Shinta Widyastuti (IKRA-ITH ABDIMAS, 2023)
The head of Tanjungsari Village, Tanjungsari sub-district, Bogor Regency in his program wants toimprove the economy of its citizens, currently villagers still depend on the economy for agricultural products,however there are 8.5% or 118 family heads are MSME actors. The location of Tanjungsari Village which isonly 75 km from the Indonesian Capital City makes this village's advantage to access raw materials andmarket MSME products. Currently, the type of MSME industry in Tanjungsari Village is engaged in theindustry of bags, wallets, sandals, shoes, wood lathes, wood products, and coffee with an average turnoveror gross income of IDR 50 million/month. The majority of raw materials for the bags, wallets, sandals, andshoes industries are imported from Jakarta, by utilizing the remaining materials from manufacturers inJakarta to be processed into other products, as well as other raw materials. The problems experienced byMSME actors often run out of business capital because all business turnover is used for daily householdconsumption. Every business activity has not been recorded so that it is not possible to plan for competitivepricing, analysis of performance achievements and improvements needed to further improve the financialperformance of MSMEs. The main problem faced by MSME actors requires a solution in the form of applyingsimple accounting because of the limited knowledge of MSME actors, so this community service activity iscarried out with the aim of economic empowerment through assistance in implementing simple accountingon MSMEs in Tanjungsari Village Community. MSME actors were given training in preparing simple financial reports using a spreadsheet, and were assisted directly for practice from making accountingjournals to financial reports using laptop media. As many as 97% of participants in Tanjungsari VillageMSMEs stated that the training conducted by the community service team was beneficial for their business